2022
DOI: 10.1002/bit.28221
|View full text |Cite
|
Sign up to set email alerts
|

All‐in‐one microfluidic design to integrate vascularized tumor spheroid into high‐throughput platform

Abstract: The development of a scalable and highly reproducible in vitro tumor microenvironment (TME) platform still sheds light on new insights into cancer metastasis mechanisms and anticancer therapeutic strategies. Here, we present an all-in-one injection molded plastic array three-dimensional culture platform (All-in-One-IMPACT) that integrates vascularized tumor spheroids for highly reproducible, high-throughput experimentation. This device allows the formation of self-assembled cell spheroids on a chip by applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…For in vitro vasculature formation, generally seeded at a density between 5 to 10 million cells/mL, together with supporting cells. Fibroblasts are the most widely used cell stromal cells, although other cell types have also been used depending on the microenvironment to be mimicked ( 13 18 ). The main reason for incorporating stromal cells is to support the formed microvasculature, which will otherwise regress after initial formation in the EC monoculture ( 19 ).…”
Section: Vascularization Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For in vitro vasculature formation, generally seeded at a density between 5 to 10 million cells/mL, together with supporting cells. Fibroblasts are the most widely used cell stromal cells, although other cell types have also been used depending on the microenvironment to be mimicked ( 13 18 ). The main reason for incorporating stromal cells is to support the formed microvasculature, which will otherwise regress after initial formation in the EC monoculture ( 19 ).…”
Section: Vascularization Strategiesmentioning
confidence: 99%
“…Kim et al. ( 18 ) recently developed an all-in-one IMPACT device, where spheroid formation and vascularization can be performed in the same device ( Figure 3A ). By injecting a small volume of cell suspension, the droplet was maintained by surface tension.…”
Section: Therapeutic Screeningmentioning
confidence: 99%
“…The platform has the format of a 96-well plate and the size of a slide glass (1 inch 3 inches). The platform has 8 identical wells, each of which consists of 2 parts: a spheroid formation area and a cell culture region [28]. Both parts are designed to pattern a liquid for spheroid formation and reconstruction of the 3D microenvironment.…”
Section: Schematic Of the Platform And The Experimentsmentioning
confidence: 99%
“…vascular networks, and performed experiments using 4 concentrations (1.25 mg/mL, 2.5 mg/mL, 5 mg/mL, and 10 mg/mL) of fibrin gel and control (2.5 mg/mL without tumor spheroids) to construct angiogenesis models. For tumor spheroids, we used gastric cancer PDCs that were used in the previous study [28]. Through the sample images that were obtained from confocal microscopy, we observed that tumor spheroid angiogenesis in 2.5 mg/mL fibrin gel showed the most sprouted vascular network compared to other concentrations and the control group (Fig.…”
mentioning
confidence: 95%
“…With the continuous development of microfabrication technology, microfluidic tumor–vessel chips not only help to precisely arrange the spatial distribution of cellular components in vitro but can also apply biomechanical and biochemical stimuli, including blood flow and growth factor gradient, thereby reproducing the interaction between the heterotypic tumor and TME with high fidelity. For example, Haase et al reported an on-chip 3D-vascularized tumor model for drug examination in a TME within a large bed of perfusable vasculature. , They demonstrated that the dose-dependent effect of anticancer drugs on tumor activity was significantly affected by the form of vascular infusion administration. Meanwhile, great strides have also been made in the field of biomaterials. , As a representative biomaterial, GelMA has been widely used in the regenerative medicine field for 3D cell culture. , Various organ models have been successfully established in GelMA, which demonstrate its good biocompatibility. ,, Antunes et al reported an in-air production of tumor spheroid-laden GelMA microgel to expedite drug screening, where GelMA was involved as tumor–ECM .…”
Section: Introductionmentioning
confidence: 99%